2006
DOI: 10.1210/jc.2005-1923
|View full text |Cite
|
Sign up to set email alerts
|

Aromatase Inhibitors for Ovulation Induction

Abstract: Preliminary evidence suggests that AIs may replace CC in the future because of similar efficacy with a reduced side effect profile. Although worldwide experience with AIs for ovulation induction is increasing, at present, definitive studies in the form of randomized controlled trials comparing CC with AIs are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
153
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(163 citation statements)
references
References 90 publications
4
153
2
4
Order By: Relevance
“…This hormonal profile, against expectations, 6 probably led to a thinner endometrium during the midluteal phase. Our previous study 18 showed that a higher baseline level of sex hormone-binding globulin, as compared with a lower level, and a lower free androgen index at baseline, as compared with a higher index, were associated with an increased live-birth rate.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…This hormonal profile, against expectations, 6 probably led to a thinner endometrium during the midluteal phase. Our previous study 18 showed that a higher baseline level of sex hormone-binding globulin, as compared with a lower level, and a lower free androgen index at baseline, as compared with a higher index, were associated with an increased live-birth rate.…”
Section: Discussioncontrasting
confidence: 46%
“…5 Aromatase inhibitors, which block estrogen synthesis, directly affect hypothalamic-pituitary-ovarian function and theoretically might increase pregnancy rates. 6 Potential advantages of aromatase inhibitors over selective estrogen-receptor modulators include a more physiologic hormonal stimulation of the endometrium, a lower multiple-pregnancy rate through singlefollicle recruitment, a better side-effect profile with fewer vasomotor and mood symptoms, and more rapid clearance, thus reducing the chances of periconceptional exposure. 6 However, potential fetal teratogenicity remains a concern with letrozole (see the Supplementary Appendix, available with the full text of this article at NEJM.org).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A single dominant follicle and monoovulation should occur in most cases [8]. In the endometrium, estrogen receptors may be upregulated, resulting in rapid endometrial growth once estrogen secretion is restored following clearance of Letrozole [9].…”
Section: Discussionmentioning
confidence: 99%
“…The use of aromatase inhibitors (AI) was only 8 %. This is interesting as AIs have been promoted by some as especially advantageous in ovulation induction of the PCOS patient [2,7,10]. Even though AIs appear to be safe in terms of fetal teratogenic risks [15], Novartis, the producer of Letrozole, states that it is only indicated for postmenopausal women and it is contraindicated in women who may become pregnant (http:// www.pharma.us.novartis.com/product/pi/pdf/Femara.pdf).…”
Section: Discussionmentioning
confidence: 99%